Similar and Different Gray Matter Deficits in Schizophrenia Patients and Their Unaffected Biological Relatives - Xiao, Yuan; Lui, Su; Zhang, Wenjing; Yao, Li; Gong, Qiyong (Frontiers in Psychiatry, 2013)
Neuroimaging studies have revealed significant reductions in the grey matter of several brain regions in patients with schizophrenia, a neuropsychiatric disorder with high hereditability. However, it is unclear whether unaffected relatives have grey matter abnormalities in common with their affected relatives, which may relate to susceptibility to developing schizophrenia. To address this issue, we conducted two separate meta-analyses of voxel-based morphometry to investigate grey matter abnormalities in schizophrenia patients and their unaffected relatives. One meta-analysis compared a patient group with healthy controls, whereas the other meta-analysis compared the unaffected relatives with healthy controls. Eight studies comprising 495 patients with schizophrenia, 584 unaffected relatives of patients and 596 healthy controls were systematically included in the present study. Compared to healthy controls, the patient group showed decreased grey matter in the right cuneus, the right superior frontal gyrus, the right insula and the left claustrum and increased grey matter in the bilateral putamen, the right parahippocampal gyrus, the left precentral gyrus, the left inferior temporal gyri and the right cerebellar tonsil. The comparison between unaffected relatives and healthy controls showed a grey matter reduction in the left claustrum, the bilateral parahippocampal gyri, the left fusiform gyrus, the right inferior temporal gyrus, and the bilateral medial prefrontal cortices, whereas increased grey matter was observed in the right hippocampus, the right fusiform gyrus, the right precentral gyrus and the right precuneus. Thus, our meta-analyses show that the grey matter changes in schizophrenia patients and their unaffected relatives are largely different, although there is subtle overlap in some regions.